PSYCHOLOGICAL WELL-BEING AMONG INDONESIAN STUDENTS STUDYING ABROAD - Suryane Sulistiana Susanti; Suryane Sucaesaria Supradaniati (Idea Nursing Journal, 2018)
One of the most important elements of academic success is determined by the conditions of the students’ psychological well-being. Previous studies suggested that psychological well-being contributed to individual adjustment, which is the key to academic success. The present study aims to identify psychological well-being among postgraduate Indonesian students studying in the United Kingdom (UK). This is a descriptive explorative study with 75 Indonesian students studying across the UK by utilising questionnaires. The result confirms that psychological well-being among the Indonesian postgraduate students studying in the UK categorised in a high level (69.3%). The study indicated the dimensions of psychological well-being from the respondents were in high autonomy (54.7%) but low environmental mastery (53.3%), high personality development (58.7%), high positive relationship with others (56.0%), high purpose of life (56.0%) and low self-acceptance (52.0%). The Indonesian postgraduate students studying in the UK had a high level of psychological wellbeing especially in terms of their personality development. The study suggests to increase environmental mastery and self-acceptance by strengthening the Indonesian student organisation activities with peer- support and building relationship with both Indonesian and international students in the UK and worldwide. This will increase their insight as international students and learn to cope and minimise stressful life events during their study period.Keywords: Psychological Well-being, Indonesian, Students, Education